Os exercícios aeróbio e resistido melhoram a memória espacial de ratos por mecanismos diferentes - Cassilhas, Ricardo Cardoso [UNIFESP] (2011)
A growing body of scientific evidence indicates that exercise has a positive impact on human health and on neurological health in particular. Effects such as increased BDNF and IGF-1 neurotrophic activity are induced by aerobic exercise and appear to influence hippocampal neurons, leading to improved spatial learning and memory. However, nothing is known about the effect of resistance exercise on hippocampus-dependent memory or whether the cellular pathways associated with aerobic exercise are also activated by resistance training. Objective: we therefore tested whether spatial learning and memory in rats is similarly enhanced by aerobic or resistance exercise and whether the cellular signals involved are similar, focusing on the BDNF/ TrKB and IGF-1/ IGF-1R pathways. Material and Methods: Adult male Wistar rats underwent eight weeks of aerobic training on a treadmill (AERO group) or resistance training on a vertical ladder (RES group); control and sham groups were also included. After the training period, both the AERO and RES groups showed improved learning and spatial memory. In addition, the BDNF/TrkB/CaMKII pathway had a higher activity in the AERO group than in the RES group. In contrast, the RES group showed greater activation of the IGF-1/IGF-1R/AKT pathway. Moreover, the two exercise groups had similar increases in synapsin and synaptophysin expression. Conclusions: We therefore conclude that, in rats, both aerobic and resistance training for eight weeks increases learning and spatial memory in a similar manner. However, the two forms of exercise seem to employ at least partially divergent mechanisms. Specifically, aerobic exercise modulates neuroplasticity selectively via the BDNF/TrkB pathway by activating CaMKII and stimulating the synthesis of synapsin and synaptophysin. In contrast, resistance training appears to increase synapsin and synaptophysin expression via the IGF-1/IGF-1R pathway.